Silylated Zeolites With Enhanced Hydrothermal Stability for the Aqueous-Phase Hydrogenation of Levulinic Acid to γ-Valerolactone - Vu, Hue-Tong; Harth, Florian M.; Wilde, Nicole (Frontiers in Chemistry, 2018)
A systematic silylation approach using mono-, di- and trichlorosilanes with different alkyl chain lengths was employed to enhance the hydrothermal stability of zeolite Y. DRIFT spectra of the silylated zeolites indicate that the attachment of the silanes takes place at surface silanol groups. Regarding hydrothermal stability under aqueous-phase processing conditions, i.e., pH ≈ 2, 473 K and autogenous pressure, the selective silylation of the zeolite surface using monochlorosilanes has no considerable influence. By using trichlorosilanes, the hydrothermal stability of zeolite Y can be improved significantly as proven by a stability test in an aqueous solution of 0.6 M levulinic acid (LA) and 0.2 M formic acid (FA) at 473 K. However, the silylation with trichlorosilanes results in a significant loss of total specific pore volume and total specific surface area, e.g., 0.35 cm3 g-1 and 507 m2 g 1 for the silylated zeolite Y functionalized with n octadecyltrichlorosilane compared to 0.51 cm3 g 1 and 788 m2 g-1 for the parent zeolite Y. The hydrogenation of LA to γ valerolactone (GVL) was conducted over 3 wt.-% Pt on zeolite Y (3PtY) silylated with either n octadecyltrichlorosilane or methyltrichlorosilane using different reducing agents, e.g., FA or H2. While in the stability test an enhanced hydrothermal stability was found for zeolite Y silylated with n octadecyltrichlorosilane, its stability in the hydrogenation of LA was far less pronounced. Only by applying an excess amount of methyltrichlorosilane, i.e., 10 mmol per 1 g of zeolite Y, presumably resulting in a high degree of polymerization among the silanes, a recognizable improvement of the stability of the 3 PtY catalyst could be achieved. Nonetheless, the pore blockage found for zeolite Y silylated with an excess amount of methyltrichlorosilane was reflected in a drastically lower GVL yield at 493 K using FA as reducing agent, i.e., 12% vs. 34% for 3PtY after 24 h.